The Relationship Between Social Capital Perceived Social Support and The Women's Mental Health in Sanandaj: a Community-Based Study - Maryam Akbari; Sarisa Najafi; Haidar Nadrian (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Considering the role of women in the family and society, development of societies is strongly influenced by the health especially the women's mental health. The aim of this study was to investigate the relationships between social capital and perceived social support with mental health among women in Sanandaj-Iran. Methods: In this cross-sectional study, 392 women aged 18 years and over were selected by multi-stage random sampling in Sanandaj (1394) General Health Questionnaire-12 (GHQ-12), Social Capital Questionnaire (SCQ) and Social Support Questionnaire (SSQ) were delivered and completed by the respondents. Data were analyzed applying SPSS-v.16 for Windows. Results: The majority of the women had a bachelors'degree (48.7%), married (53.3%) and a housewife (26.3%), Pearson Correlation Coefficient test showed a significant and positive association between the three variables (r > 0.350, p < 0.01). Linear Regression analysis indicated that both, social capital and perceived social support significantly predicted 30% of mental health changes that thesocial capital was the stronger predictor.   Conclusion: The women surveyed in Sanandaj had a moderate level of mental health and perceived social support and the level of social capital was weak. Interventional efforts to promote their mental health, emphasizing social capital, should be priorities of the authorities. Also, family members training is suggested as the main strategy for decision-makers and policy makers in the field of women's health.